Long‐term renal function after treatment for unilateral, nonsyndromic Wilms tumor. A report from the St. Jude Lifetime Cohort Study. Issue 10 (24th July 2020) - Green, Daniel M.; Wang, Mingjuan; Krasin, Matthew J.; Davidoff, Andrew M.; Srivastava, DeoKumar; Jay, Dennis W.; Ness, Kirsten K.; Shulkin, Barry L.; Spunt, Sheri L.; Jones, Deborah P.; Lanctot, Jennifer Q.; Shelton, Kyla C.; et al.
Abstract: Background: The impact of specific treatment modalities on long‐term renal function and blood pressure among adult survivors of Wilms tumor (WT) has not been well documented. Methods: Among 40 WT survivors and 35 noncancer controls, we estimated the glomerular filtration rate (eGFR) using the Chronic Kidney Disease‐Epidemiology (CKD‐EPI) equations with and without cystatin C, obtained 24‐hour ambulatory blood pressure readings, and, among survivors only, measured 99m Tc diethylenetriamine pentaacetic acid (DTPA) plasma clearance. Survivors were treated with unilateral nephrectomy and nonnephrotoxic chemotherapy. Twenty received whole abdomen radiation therapy (WART) [median –16.5 Gray (Gy)], and 20 received no radiation therapy. Pairwise comparisons between survivors treated with and without WART, and each group to controls were performed using two‐sample t tests. Results: Twenty‐six (65%) WT survivors were female, and 33 (83%) were non‐Hispanic white. GFR estimated with creatinine or creatinine + cystatin C was decreased among irradiated survivors compared with controls. No irradiated or unirradiated participant had an eGFR (creatinine + cystatin C) < 60 mL/min/1.73 m 2 . The prevalence of hypertension was significantly increased among unirradiated (25%) and irradiated survivors (35%) compared with controls (0%). Of the 24‐hour ambulatory blood pressure monitoring parameters evaluated, only mean sleep period diastolic blood pressure load of those who received WART was significantly different from that of controls. Conclusions: Chronic kidney disease was infrequent in long‐term survivors of unilateral nonsyndromic WT, whether treated with WART or no radiation. The prevalence of hypertension was increased in both groups compared with controls, emphasizing the need for ongoing monitoring of renal and cardiovascular health.